Diversity of Herbs and Lianas in The Suranadi Tourism Park Area, West Lombok Regency in 2024 - Majdi, Mohammad Zainul; Raksun, Ahmad; Mertha, I Gde; Sukarso, A. A. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
One of the conservation forests with diverse types of flora and tropical forests that are evenly distributed is Suranadi Nature Tourism Park. The types of herbs and lianas are rare plants that are rarely studied in the Suranadi Nature Tourism Park Area. This study aims to describe the species of Herba and Liana plants in the Suranadi Nature Tourism Park area of West Lombok Regency. The type of research used is quantitative research that is descriptive explorative with exploration or survey methods. The research data were analyzed quantitatively which would then be described and calculated using the Shannon-Wieener index to measure species diversity. The results of the study at the location were: there were 13 species from 11 families found in Herba plants and there were 9 species from 7 families found in Liana plants. The results of this study obtained a richness index of 2.49 for 13 types of herbs and -58.13 for 9 types of lianas found and entered the medium-low richness category. This study proves that the fewer types of plants found in an area, the lower the richness index value.